Are happier adolescents more willing to protect the environment? Empirical evidence from Programme for International Student Assessment 2018 - Zhang, Min; Zhang, Weidong; Shi, Yong (Frontiers in Psychology, 2023)
A large number of existing studies have discussed the potential factors affecting pro-environmental behaviors (PEBs) in adolescents. However, few studies have focused on the possible impact of adolescents’ subjective well-being (SWB) on their PEBs. Why and how adolescents’ SWB affects their PEBs remains a puzzle. To unravel this puzzle, this paper aims to establish a suitable instrumental variable (IV) to correctly estimate the contribution of adolescents' SWB to their PEBs. Using the international data from the OECD’s Programme for International Student Assessment 2018, we construct a unique dataset of eight countries or economies, which includes 56,374 samples related to the SWB and PEBs of 15-year-old students. In this paper, the days of physical education classes in school per week are used as the IV. Through a two-stage least squares method, we find that the contribution of adolescents’ SWB to PEBs is significantly positive. We also find that the pathway by which SWB improves PEBs works through adolescents’ self-efficacy. Furthermore, the results indicate that the positive impact of SWB on PEBs is more pronounced among adolescents with better peer relationships and stronger multicultural values. Our findings highlight the influence of positive affects in cultivating adolescents' PEBs and the importance of growing up surrounded by happiness.